Faculties’ Perception on Semester System at TU Affiliated Colleges, Nepal - Sherpa, Dawa; Baraily, Khagendra (AMC Journal, 2022)
The total educational session completing in a half of the year is simply referred as semester system. In semester system the total educational activities are based upon the project basis. This study aimed at exploring the perceptions of faculties about the semester system adopted by a Tribhuvan University (TU) affiliated college in Nepal. It also dug out the faculties’ experience of pedagogical transformation in higher education. For the sake of their world views, an interpretive paradigm was employed. In this philosophical orientation, subjective reality is an ontological position and multiple realities are epistemological standpoints. This study employed qualitative research method. Narrative inquiry was chosen as the research design. Four participants from the TU-affiliated colleges had been taken purposively from the campus located outside the Kathmandu Valley. An in-depth interview was conducted with research participants in their natural settings without any interruption. The result revealed that the faculties’ perception of the semester system was diverse in nature. The student behaviors, faculty behaviors, and unpreparedness of teachers and administration seemed to be more challenging and unfruitful. The effectiveness of the semester system can contribute not only to pedagogical transformation but also to global knowledge. Through the semester system, the whole faculties and students are self-empowered and seek to understand the world through the effort of digital technology.